Einstein and Germany - Mujahid Kamran (Lahore Sang-e-Meel Publications, 2013)
Albert Einstein, 1879-1955, German theoretical physicist and Nobel Prize laureate
Include Bibliography and Index
Keywords: Physicists -- Germany -- Einstein, Albert, 1879-1955